Integrity management in community-based water tenure in Kajiado County, Kenya - Keega, M.; Manishimwe, E.; Schreiner, B.; van Koppen, Barbara; Amarnath, Giriraj (International Water Management Institute (IWMI), 2023)
Smallholder production systems in low-income countries suffer the most from the impacts of climate change but receive the least benefit from climate adaptation programs. This is due to governance structures that make it difficult for governments and organizations to effectively reach marginalized communities. Technical, financial, and institutional support is provided in vertical siloes, limiting coordination between national government departments and hindering integrated climate interventions. Additionally, top-down support frameworks overlook the horizontal governance structures of rural communities, missing opportunities to recognize and build on their age-old knowledge and coping strategies to deal with climate variability. The Water Integrity Network (WIN) advocates for integrity in polycentric water governance through transparency, accountability, participation, and corruption prevention across scales. WIN partners with national governments and NGOs to implement the Integrity Management Tool (IMT) for small water supply systems (SWSS). The IMT-SWSS aims to improve management and governance practices, increase customer satisfaction, and comply with regulations. In Kenya, where only half of the rural population has access to improved water sources, WIN has collaborated with policy makers and implemented the IMTSWSS to support sustainable operation and maintenance of small-scale water supply systems, among other, in three systems in Mailua Community in Kajiado South County. This Maasai area was selected for the present study. The study aims to analyse the integrity perspective for small-scale water supply systems within horizontal polycentric governance at the local community scale. The focus is on how the community manages multiple sources of water to meet their domestic and productive needs, and on the decision-making process between water users, their leaders, and government institutions. The Mailua Community has multiple gravity water systems, boreholes, and water vendors. Representatives of the water supply systems participated in a training on the IMT-SWSS, and an umbrella committee was set up to represent the interests of the systems to other governance structures. The study methodology included a literature review of both published and grey literature for this particular area. The field research was done in two phases. Phase one involved participatory mapping, transect walks, interviews with key informants and focus group discussions. Phase two included further exploration of thematic areas with significant impact on water use and polycentric governance structures that were identified through data analysis during phase one. This included the planning of the new Namanga Dam, and the two-way vertical integration of top-down and bottom-up governance.